A facile graphene oxide based sensor for electrochemical detection of prostate anti-cancer (anti-testosterone) drug flutamide in biological samples. Issue 41 (12th May 2017) - Karthik, R.; Govindasamy, Mani; Chen, Shen-Ming; Chen, Tse-Wei; Vinoth kumar, J.; Elangovan, A.; Muthuraj, V.; Yu, Ming-Chin
Abstract : An electrochemical sensor based on graphene oxide modified glassy carbon electrode for the determination of anti-cancer drug flutamide. Abstract : A novel electrochemical sensor based on graphene oxide (GO) modified glassy carbon electrode (GCE) has been successfully developed for the determination of anti-cancer drug flutamide for the first time. The morphology and structure of the prepared GO were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), UV-visible spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), field emission-scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM). The electrochemical properties of the GO were studied by electrochemical impedance spectroscopy (EIS). GO modified GCE was fabricated and utilized to study the electrochemical performance of flutamide by cyclic voltammetry (CV) and linear sweep voltammetry (LSV). As an electrochemical sensor, GO modified GCE exhibited strong electrocatalytic activity towards the reduction of flutamide. Interestingly, the electrochemical sensor displayed an excellent current response for the detection of flutamide with wide linear response range, excellent limit of detection and good sensitivity of 0.009 to 1.9 μM, 6 nM and 29.55 μA μM −1 cm −2, respectively. The proposed sensor has good repeatability, reproducibility, stability and selectivity even in the presence of biologically co-interfering substances. GO modified GCE sensor was successfully used for the detection of flutamide (spiked) in various blood serum samples.